Site-specific mutagenesis identifies three cysteine residues in the cytoplasmic tail as acylation sites of influenza virus hemagglutinin. - Veit, M (1991)
The hemagglutinin (HA) of influenza virus is a type I transmembrane glycoprotein which is acylated with long-chain fatty acids. In this study we have used oligonucleotide-directed mutagenesis of cloned cDNA and a simian virus 40 expression system to determine the fatty acid binding site in HA and to examine possible functions of covalently linked fatty acids. The results show that the HA is acylated through thioester linkages at three highly conserved cysteine residues located in the cytoplasmic domain and at the carboxy-terminal end of the transmembrane region, whereas a cysteine located in the middle of the membrane-spanning domain is not acylated. Mutants lacking fatty acids at individual or all three attachment sites acquire endoglycosidase H-resistant oligosaccharide side chains, are cleaved into HA1 and HA2 subunits, and are transported to the plasma membrane at rates similar to that of wild-type HA. All mutants are membrane bound and not secreted into the medium. These results exclude transport signal and membrane-anchoring functions of covalently linked fatty acids for this integral membrane glycoprotein. Furthermore, lack of acylation has no obvious influence on the biological activities of HA: cells expressing fatty acid-free HA bind to and, after brief exposure to mildly acidic pH, fuse with erythrocytes; the HA-induced polykaryon formation is not impaired, either. Other possible functions of covalently linked fatty acids in integral membrane glycoproteins which cannot be examined in conventional cDNA expression systems are discussed.